Examining +2 Level Students’ Email Writing Proficiency: A Critical Analysis and Recommendations - Gurung, Raj Kumar (Dhaulagiri Journal of Contemporary Issues, 2023)
This paper examines +2 level students’ email writing proficiency critically and recommends the necessary tips for improvements. Email writing has become a crucial aspect of teaching and learning activities in EFL classes. It is the quickest means of communication for bulk messaging. The practice of post offices is almost obsolete. The postman used to deliver letters to people from one place to another place and the delay was common. Now, in the digital age, email writing has become the fastest means of communication for disseminating the messages to the recipients. Despite this, both the teachers and students do not take the email writing process as a crucial matter. The findings of the study show that +2 level students write emails like a letter in their exam papers. They can do the same in reality as well. Their teachers should instruct them properly. Email writing is not as simple as the teachers and students think. Email writing does not only inform, it also persuades the recipients. The study aims at empowering the +2 level students’ email writing proficiency by suggesting with required methods, techniques and tips. Their skills are not well patterned because their teachers do not instruct them sincerely. Therefore, both the teachers and students should tackle this email writing with the exact formats and methods. The study is qualitative research and it adopts the descriptive survey methods for the analysis of their email writing skills.